SAT0123 Evidence-Based Recommendations for the Management of Comorbidities in Rheumatoid Arthritis, Psoriasis and Psoriatic Arthritis: A Systematic Literature Search and Expert Opinion. (10th June 2014) - Roubille, C.; Richer, V.; Starnino, T.; McCourt, C.; McFarlane, A.; Fleming, P.; Siu, S.; Kraft, J.; Lynde, C.; Pope, J.; Gulliver, W.; Keeling, S.; et al.
Abstract : Background: Comorbidities such as cardiovascular diseases (CVD), cancer, osteoporosis and depression in rheumatoid arthritis (RA), psoriatic arthritis (PsA) and psoriasis (PsO) are often under-recognized, and recommendations may improve their identification and treatment. Objectives: The Canadian Dermatology-Rheumatology Comorbidity Initiative reviewed the literature to develop practical evidence-based recommendations for management of comorbidities in RA, PsA and PsO patients. Methods: Eight questions regarding comorbidities in RA, PsA and PsO were developed. Literature was systematically searched (MEDLINE, EMBASE, Cochrane Library, and 2010-2012 ACR-EULAR-AAD-EADV abstracts), selected articles analysed and meta-analyses performed whenever possible. A meeting including rheumatologists, dermatologists, trainees/fellows and invited experts was held to develop consensus-based recommendations using a Delphi voting process with pre-specified cut-off agreement. The level of agreement was measured using a 10-point Likert scale and the potential impact of the recommendations on daily practice was considered. The level of evidence and the grade of recommendation were determined according to the Oxford levels of evidence. Results: A total of 407 out of 17, 575 articles were included in the systematic reviews. Recommendations were synthesized into 19 final recommendations ranging mainly from grade C to D, and relating to a large spectrum of comorbidities observed in clinical practice in patients with RA, PsA and PsO: CVD, obesity, osteoporosis, depression, infections and cancer. The level of agreement ranged from 80.9% to 95.8%. Conclusions: These practical evidence-based recommendations can guide management of RA, PsA and PsO and optimize outcomes. Disclosure of Interest: C. Roubille: None declared, V. Richer Grant/research support: This study was supported by an unrestricted grant from AbbVie., T. Starnino Grant/research support: This study was supported by an unrestricted grant from AbbVie., C. McCourt Grant/research support: This study was supported by an unrestricted grant from AbbVie. Salary for the fellowship in Vancouver was funded by a Fellowship from Janssen-Ortho Canada and the British Association of Dermatology., A. McFarlane Grant/research support: This study was supported by an unrestricted grant from AbbVie., P. Fleming Grant/research support: This study was supported by an unrestricted grant from AbbVie., S. Siu Grant/research support: This study was supported by an unrestricted grant from AbbVie., J. Kraft Grant/research support: This study was supported by an unrestricted grant from AbbVie. Investigator support from Abbvie, Amgen, Galderma, Janssen, Novartis, Consultant for: Abbvie, Amgen, Galderma, Janssen, Novartis, Leo Speakers bureau: Abbvie, Amgen, Galderma, Janssen, Leo, C. Lynde Grant/research support: This study was supported by an unrestricted grant from AbbVie. Investigator support: Abbvie, Amgen, Celgene, Janssen-Ortho, Novartis, Eli Lilly, Merck, Leo Pharma, Consultant for: Abbvie, Amgen, Celgene, Janssen-Ortho, Novartis, Eli Lilly, Merck, Leo Pharma, Speakers bureau: Abbvie, Amgen, Celgene, Janssen-Ortho, Novartis, Eli Lilly, Merck, Leo Pharma, J. Pope Grant/research support: This study was supported by an unrestricted grant from AbbVie. Research support from AbbVie, Actelion, Amgen, Astra Zeneca, Bayer, BMS, Celgene, Genentech, GSK, BMS, Jansen & Jansen, MedImmune, Mediquest, Novartis, Pfizer, Roche, United Chemicals Belgium, Consultant for: AbbVie, Actelion, Amgen, Astra Zeneca, Bayer, BMS, Celgene, Genentech, GSK, BMS, Jansen & Jansen, MedImmune, Mediquest, Novartis, Pfizer, Roche, United Chemicals Belgium, W. Gulliver Grant/research support: study was supported by an unrestricted grant from AbbVie. Research support from Abbott/AbbVie, Actelion, Amgen, Astellas, Bio-K, Celgene, Galderma, Janssen, LEO Pharma, Merck/Schering, Novartis, Pfizer, Roche and Valeant, Consultant for: Abbott/AbbVie, Actelion, Amgen, Astellas, Bio-K, Celgene, Galderma, Janssen, LEO Pharma, Merck/Schering, Novartis, Pfizer, Roche and Valeant, Speakers bureau: Abbott/AbbVie, Actelion, Amgen, Astellas, Bio-K, Celgene, Galderma, Janssen, LEO Pharma, Merck/Schering, Novartis, Pfizer, Roche and Valeant, S. Keeling Grant/research support: This study was supported by an unrestricted grant from AbbVie. Unrestricted educational funding received from the following:Pfizer, Janssen, Astrazeneca, Roche, Consultant for: Participated in advisory boards as consultant for:Janssen, AbbVie, Roche, Amgen, J. Dutz Grant/research support: This study was supported by an unrestricted grant from AbbVie. Research support Abbvie, Centocor, Janssen- Ortho, Novartis, ONO Pharmaceuticals, Roche, Consultant for: Janssen-Ortho, AbbVie Amgen, Leo, Roche Speakers bureau: Janssen-Ortho, AbbVie Amgen, Leo, L. Bessette Grant/research support: This study was supported by an unrestricted grant from AbbVie. Research support AbbVie, UCB, Janssen, and Amgen. Consultant for: AbbVie, UCB, Janssen, and Amgen, Speakers bureau: AbbVie, UCB, Janssen, and Amgen, R. Bissonnette Grant/research support: This study was supported by an unrestricted grant from AbbVie. Research grants and honoraria AbbVie, Amgen, Celgene, Eli-Lilly Galderma, Incyte, Janssen, Leo Pharma, Merck, Novartis, Pfizer, Tribute, Consultant for: AbbVie, Amgen, Celgene, Eli-Lilly Galderma, Incyte, Janssen, Leo Pharma, Merck, Novartis, Pfizer, Tribute, B. Haraoui Grant/research support: This study was supported by an unrestricted grant from AbbVie. Grant support from Abbvie, Amgen, BMS, Celgene, Janssen, Pfizer, Roche, UCB, Consultant for: Abbvie, Amgen, BMS, Celgene, Janssen, Pfizer, Roche, UCB DOI: 10.1136/annrheumdis-2014-eular.2274